Law, Politics, and Morality : European Perspectives II.:On Knowledge and Adjudication of National and European Law. - Ferrer Beltrán, Jordi (Schriften zur Rechtstheorie - 215/II., 2011)
Hauptbeschreibung Teaching and study of law is based on the premises of formal dogma. Discussion centres on what the law says, and less on the Instruments enabling its application, such as legal argumentation and reasoning. The approach to the new legal and institutional challenges facing the European Union is not immune to this problem. Little public attention is paid to actual law emanating from EU institutions, and even less to its application. However, at least three issues of vital importance can easily be seen to originate in this field: (1) Does legal harmonisation among EU coun.